Menggali Akar Pemikiran Kelompok Inkar Sunnah - Syaifudin (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
This study comprehensively examines the concept of Inkar Sunnah, a movement that rejects the Sunnah of Prophet Muhammad (PBUH) as a legitimate source of Islamic law after the Qur'an. The research aims to explore the definition, historical emergence, forms of thought, and arguments promoted by Inkar Sunnah groups in both classical and modern contexts, including the development of the movement in Indonesia. Using a qualitative method with a library research approach, the study analyzes classical and contemporary literature. The findings reveal that the arguments presented by Inkar Sunnah proponents, whether textual or rational, are weak both methodologically and theologically. This ideology poses a serious threat to the authority of Sunnah in Islamic practice. Therefore, strengthening Islamic literacy and systematic hadith education is essential to counter the spread of this movement within society.